Sequential Saccharification and Simulataneous Fermentation (SSSF) of Sago “Hampas” for the Production of Bioethanol. - Berry Rence, Senawi (Universiti Malaysia Sarawak, UNIMAS, 2013)
Bioethanol is one of the sustainable and renewable energy sources to replace fossil fuel. In this study, bioethanol was produced from sago hampas by using Saccharomyces cerevisiae. Sequential saccharification and simultaneous fermentation (SSSF), a modified version of simultaneous saccharification and fermentation (SSF) was performed on the sago hampas in different concentration which is 2.5% (w/v) and 5.0% (w/v) for five days. The samples taken from fermentation were analysed via DNS reducing sugar assay, phenol-sulphuric total carbohydrate assay and High Performance Liquid Chromatography (HPLC). This study has shown that ethanol was able to be produce from sago hampas using S. cerevisiae via SSSF. From the results obtained, 5.0% sago hampas give the highest ethanol yield which is 77.43% with a significant ratio of lactic acid and acetic acid